Real-Life Diagnostic Accuracy of MRI in Prenatal Diagnosis - Manuel Recio Rodríguez; Cristina Andreu-Vázquez; Israel J. Thuissard-Vasallo; Raquel Cano Alonso; Carmina Bermejo López; Ines Tamarit Degenhardt; Pilar Martínez Ten (Radiology Research and Practice)
There is some controversy about the value of fetal MRI in prenatal diagnosis, and most of the studies examine its accuracy in central nervous system (CNS) pathology. The objective of this retrospective study was to assess the diagnostic accuracy and usefulness of fetal MRI in the prenatal diagnosis of central nervous system (CNS) pathology and non-CNS pathology. Patients referred to the Radiology Department between 2007 and 2018 for a fetal MRI after detection of an anomaly in the fetal ultrasound, a high-risk pregnancy, or an inconclusive fetal ultrasound (n = 623) were included in the study. Postnatal diagnosis was used to assess the diagnostic accuracy of MRI. Fetal MRI was considered to provide additional information over fetal ultrasound when findings of the fetal MRI were not detected in the fetal ultrasound or when established a pathological condition that was not detected in the fetal ultrasound. Fetal MRI provided useful information for the perinatal management and prognosis over fetal ultrasound when findings of the fetal MRI changed the postnatal prognosis, leaded to the decision to legally terminate the pregnancy, changed prenatal or postnatal follow-up, or helped in the planning of prenatal or postnatal treatment. Fetal MRI offered an accurate diagnosis in 97% of cases (compared to 90.4% of fetal ultrasound; p<0.001). Concordance between fetal ultrasound and fetal MRI was 92.1%. Fetal MRI provided additional information over fetal ultrasound in 23.1% of cases. In 11.6% of cases, the information was useful for the perinatal management and prognosis. In 45 cases (7.2%), fetal MRI was the only accurate diagnosis. In conclusion, fetal MRI has a superior diagnostic accuracy, especially in CNS pathology, and provides additional useful information in CNS, thoracic, and abdominal pathology.